Reseñas - D’Amico, Claudia; Piemonte, Gustavo A. (Patristica et Mediævalia, 1998)
FERNANDO DOMÍNGUEZ / JAIME DE SALAS (eds), Constantes y fragmentos del pensamiento luliano. Actas del Simposio sobre Ramón Llull en Trujillo, 17-20 septiembre 1994. GERD VAN RIEL / CARLOS STEEL / JAMES MCEVOY (eds), Iohannes Scottus Eriugena, The Bible and Hermeutics. Proceedings of the 9th International Colloquium of the Society for the Promotion of Eriugenan Studies.